Pendidikan Anak Berkebutuhan Khusus Fisik pada Anak Tunawicara di TK Harsya Ceria Banda Aceh - Rizka Rahadatul Aisy; Hijriati Hijriati; Fitria Fitria; Ghina Raudhatul Jannah; Misna Yani (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
This study aims to analyze the education of children with special physical needs, particularly children with speech impairment, at TK Harsya Ceria Banda Aceh. The study used a qualitative method with a descriptive approach to describe the learning process, fulfillment of physical needs, teacher assistance, family support, and obstacles faced in inclusive education. Data were collected through observation, interviews, and documentation involving school principals, teachers, parents, and children with speech impairment. The results showed that TK Harsya Ceria has implemented inclusive education by providing equal learning opportunities for children with special needs alongside regular students. Teachers use visual media, body language, educational games, and individual assistance to support children’s communication and learning processes. Family support also plays an important role in developing children’s independence, communication skills, and social interaction. However, several obstacles were found, including communication barriers, limited facilities, lack of special assistants, and high therapy costs. Therefore, collaboration between schools, families, health workers, and the government is needed to support the optimal development of children with speech impairment in inclusive education environments.